Resolving the last combination in Tovomitidium, a synonym for Tovomita (Clusiaceae) - Marinho, Lucas C.; Fiaschi, Pedro; Amorim, André M. (Phytotaxa, 2018)
Tovomitidium (Clusiaceae) is a small genus from the Amazon Forest, described to accommodate T. clusiiflorum plus one segregated species from Tovomita, T. speciosum. Some authors considered Tovomitidium as synonymous with Tovomita, but online databases still point to Tovomitidium as a valid genus within the Clusiaceae. Herein, we provide comments on the two species of Tovomitidium and present arguments to reinforce our opinion they belong in Tovomita. Additionally, a new combination, synonym and lectotype are presented.